The Effect Of Service Quality And Product Quality On Customer Satisfaction Baraya Collection - Muhammad Arsyad; H. Ari Arisman; Barin Barlian (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the effect simultaneously and partially between Service Quality and Product Quality on Baraya Collection Customer Satisfaction. The research method used has a survey method with a quantitative approach. The sampling technique used the saturated sample method with a total sample of 100 people. Data collection techniques using online and offline questionnaires. The data used has primary data. The analytical tool used in this study is multiple regression using SPSS version 26. The results of the study show that simultaneously service quality and product quality have a significant effect on customer satisfaction. Partially, service quality has a significant effect on consumer satisfaction. Partially product quality has a significant effect on customer satisfaction.